Circularly Polarized Slotted Microstrip Patch Antenna with Finite Ground Plane - Sanyog Rawat; K K Sharma (Universitas Sriwijaya, 2012)
In this paper a new geometry of circularly polarized patch antenna is proposed with improved bandwidth. The radiation performance of proposed patch antenna is investigated using IE3D simulation software and its performance is compared with that of conventional rectangular patch antenna. The simulated return loss, axial ratio and impedance with frequency for the proposed antenna are reported in this paper. It is shown that by selecting suitable ground-plane dimensions, air gap and location of the slots, the impedance bandwidth can be enhanced upto 10.15% as compared to conventional rectangular patch (4.24%) with an axial ratio bandwidth of 4.05%.DOI:Â 10.18495/comengapp.12.097106